Faktor-Faktor yang Dominan Mempengaruhi Permintaan pada Distro Kota Denpasar - Ni Putu Rasrita Deyan; A. A. Sri Purnami; I Gusti Ayu Athina Wulandari (Warmadewa Economic Development Journal (WEDJ), 2022)
Distro is a world of self-produced clothing models, brands and also issue their own design and also their own marketing. This study is a dive into the strong factor of moderate demand at the Denpasar City level. This study peddles primary data with expolatori factor analysis techniques. This study peddles the demand factor affecting distros in Denpasar City as a whole as the main factor is that the future state consists of one approximate variable and the arousal of exactly four variables. Looking at the study of factors affecting demand in Denpasar City becomes a factor forecasting the future situation in the form of one variable and factors that are in the second position are estimates and tastes.